SPIN-OFFS VS. DIVIDENDS IN KIND. - Simon, Sidney I. (The Accounting Review, 1960)
Abstract Much attention has recently been given by the public press to the developments in the recent Government anti-trust suit against the DuPont Company and General Motors Corporation. While students of accounting are generally made quite aware of another interesting distinction in the field of corporate distributions, that of the stock dividend versus the stock split, little if any attention is given in accounting literature to their "second cousins," the subjects of this paper. In the stock dividend and the stock split, one is dealing with the problems of increasing the number of outstanding shares of a corporation's own stock. The term "dividend in kind" actually refers to any distribution by a corporation, out of earnings or retained income, of an asset other than money. The income tax treatment of such property dividends in stock, incidentally, presents a seeming paradox which is interesting from an accounting standpoint. When a corporation distributes property as a dividend in kind, its surplus is decreased by an amount equal to the cost of the property.